Final answer:
To find the value of (h o g)(-1), first calculate g(-1) which is -7 and then evaluate h(-7), which results in 50.
Step-by-step explanation:
To find (h o g)(-1), you need to do a two-step process. First, evaluate g(-1), which is the function g(x) with x replaced by -1. According to the given function g(x) = 5x - 2, when you plug in -1 you get:
g(-1) = 5(-1) - 2
= -5 - 2
= -7
Now, take this result and plug it into the function h(x), so you compute h(g(-1)), which is equivalent to h(-7). Given h(x) = x² + 1, you get:
h(-7) = (-7)² + 1
= 49 + 1
= 50
Therefore, (h o g)(-1) = 50.